The role of the interviewer in producing mode effects: Results from a mixed modes experiment comparing face-to-face, telephone and web administration - Steven Hope; Pamela Campanelli; Gerry Nicolaas; Peter Lynn; Annette Jäckle (University of Essex, Institute for Social and Economic Research (ISER), 2014)
The presence of an interviewer is hypothesised to motivate respondents to generate an accurate answer and reduce task difficulty, but also to reduce the privacy of the reporting situation.The prevalence of indicators of satisficing (e.g., non-differentiation, acquiescence, middle categories, primacy and recency, and item nonresponse) and socially desirable responding were studied experimentally across modes and also through cognitive interviewing. Results show differences between interviewer and self-completion modes: in levels of satisficing for non- differentiation, acquiescence, and middle categories and socially desirable responding. There were also unexpected findings of a CATI primacy/positivity bias and of different ways of satisficing.
Keywords: 330; Mode Effects; Interviewer presence; Satisficing; Primacy; Recency; Middle category effects; Non-differentiation; Social desirability